2018
DOI: 10.1002/ejic.201801257
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of a Mononuclear η2‐(Ge–H)palladium(0) Complex Bearing a PGeP‐Pincer‐Type Germyl Ligand: Reactivity Differences between Silicon and Germanium

Abstract: Reactivity differences between silicon and germanium as supporting ligands in PEP-pincer type palladium complexes (E = Si, Ge) were clarified by experimental and theoretical studies. An η 2 -(Ge-H)palladium(0) complex, which was synthesized and structurally characterized for the first time, exhibited higher reactivity for hydrometallation of ethylene than the silylanalogue. The resulting PGeP-ethylpalladium(II) complex was more stable than the silyl-analogue, which allowed its isolation and structural analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…It is also claried that the germyl ligand stabilizes the ethyl-Pd II state more efficiently than the silyl ligand and is suitable for reactions with formate salts under heating conditions. 72 We have also developed a selective dehydrogenative borylation reaction of alkenes with B 2 pin 2 catalyzed by PSiP-Pd complex 71 having electron decient Ar substituents on phosphorus side arms (Scheme 32). The reaction with 2 equivalents of B 2 pin 2 enables an efficient synthesis of a variety of double borylation products involving 1,1-, trans-1,2-, and cyclic-1,2diborylalkenes starting from alkenes and B 2 pin 2 , which are synthetically highly useful but not accessible with standard transition metal-catalyzed borylation reactions.…”
Section: Group 14 (E ¼ Si and Ge)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also claried that the germyl ligand stabilizes the ethyl-Pd II state more efficiently than the silyl ligand and is suitable for reactions with formate salts under heating conditions. 72 We have also developed a selective dehydrogenative borylation reaction of alkenes with B 2 pin 2 catalyzed by PSiP-Pd complex 71 having electron decient Ar substituents on phosphorus side arms (Scheme 32). The reaction with 2 equivalents of B 2 pin 2 enables an efficient synthesis of a variety of double borylation products involving 1,1-, trans-1,2-, and cyclic-1,2diborylalkenes starting from alkenes and B 2 pin 2 , which are synthetically highly useful but not accessible with standard transition metal-catalyzed borylation reactions.…”
Section: Group 14 (E ¼ Si and Ge)mentioning
confidence: 99%
“…It is also clarified that the germyl ligand stabilizes the ethyl–Pd II state more efficiently than the silyl ligand and is suitable for reactions with formate salts under heating conditions. 72 …”
Section: Catalysis Using M–e Complexes In Synthetic Reactionsmentioning
confidence: 99%
“…[1] In fact, some of these germylenes have already led to transition metal (TM) complexes containing either PGeP pincer germylene ligands (just by simple coordination) [7,8] or PGeP pincer germyl ligands (by insertion of the Ge atom into an MÀ Cl bond of the metal precursor). [2][3][4][8][9][10][11] A few PGeP pincer germyl metal complexes were already known before the appearance of metal-free PGeP germylenes, but the strategy used for their syntheses is not of general applicability because it involves the formation of a GeÀ M bond from a GeÀ C, [12,13] GeÀ H, [13,14] GeÀ Cl [15] or GeÀ F [16] bond of a germane fragment.…”
Section: Introductionmentioning
confidence: 99%
“…The current interest in investigating TM complexes containing PGeP pincer germyl ligands is associated to the highly appreciated usefulness of pincer ligands in CÀ H bond activation reactions and catalysis [17,18] and to the fact that their syntheses and reactivity have so far been scarcely investigated. [2][3][4][8][9][10][11][12][13][14][15][16] In addition some PGeP pincer complexes have been satisfactorily tested as homogeneous catalyst precursors. [13,19] In the field of PGeP pincer chemistry, we have recently shown that germylene C (Figure 1), which is based on the dipyrromethane scaffold, [4] is better suited than germylenes A [2] and B [3] (Figure 1) to form stable PGeP pincer chloridogermyl complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of heavier-group-14 elements other than silicon has also been identified as a potentially effective strategy to develop highly active catalysts. For instance, Iwasawa and Takaya have examined the catalytic activity of Pd complexes that bear PSiP or PGeP pincer-type ligands in the hydrocarboxylation of allenes, and found that the latter exhibit superior catalytic performance relative to the former [13][14][15]. However, examples of iron complexes that contain heavier-group-14 ligands, such as organogermyl ligands, remain scarce due to a lack of synthetic methods [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%